2010
DOI: 10.4995/wrs.2008.616
|View full text |Cite
|
Sign up to set email alerts
|

Native immunity and oxidative traits of growing rabbits

Abstract: AbstrAct:The evaluation of animal welfare through innate immunity (Serum Bactericidal Activity -SBA, Hemolytic Complement Assay -HCA, lysozyme) and the antioxidant status of the body (Reactive Oxygen Substances -ROS and Antioxidant Power of plasma, AP) offers a reliable prognostic and diagnostic tool. The aim of the present study was to investigate trends and correlations between some traits of innate immunity and the oxidative status of fattening rabbits at different ages. Blood samples from 120 New Zealand W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is able, on the one hand, to break down the relationship between N-acetylmuramic acid and N-acetylglucosamine as an enzyme, and on the other hand, lysozyme is able to mobilize other nonspecific factors of organism's defense. It's present in azurophilic granules and specific neutrophils grains and also monocytes and macrophages grains [17]. Similarly, serum bactericidal activity reacted to the action of above listed fodder the experimental groups in comparison to control.…”
Section: Resultsmentioning
confidence: 81%
“…It is able, on the one hand, to break down the relationship between N-acetylmuramic acid and N-acetylglucosamine as an enzyme, and on the other hand, lysozyme is able to mobilize other nonspecific factors of organism's defense. It's present in azurophilic granules and specific neutrophils grains and also monocytes and macrophages grains [17]. Similarly, serum bactericidal activity reacted to the action of above listed fodder the experimental groups in comparison to control.…”
Section: Resultsmentioning
confidence: 81%
“…Sudha et al, (2010) showed that methanol extract of moringa leaves given orally to mice at doses of 250 and 750 mg/kg stimulated both cellular and humoral immune responses. Moscati et al, (2008) reported that lysozyme at level of 27.19 μg / ml is a strong antibacterial enzyme (against Gram positive) and has a synergic action with immune humeral response, and factors of the serum complement. Moscati, et al, (2008) recorded that lysozyme value of 27.19 μg/ml as an innate immunity indicator was higher than those reported by Carroll and Martinez, (1979) in healthy rabbits (0.85 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Serum lysozyme is a strong antibacterial enzyme (against Gram⁺) that has a synergic action with immune humoral response and the serum complement (Carroll and Martínez, 1979;Moscati et al, 2008) and is related with macrophage function indicating an inflammation state.…”
Section: Resultsmentioning
confidence: 99%